Tube thoracostomy: Primary management option for empyema thoracis in children - Rajendra K Ghritlaharey; Keshav S Budhwani; Dhirendra K Shrivastava; Jyoti Srivastava (Wolters Kluwer Medknow Publications, 2012)
Aim: The aim of this study was to review our experience with tube thoracostomy in the management of empyema thoracis in children. Patients and Methods: This retrospective study included 46 children (26 boys and 20 girls) who were admitted and managed for empyema thoracis, between January 1, 2010 and December 31, 2010 at the author's department of paediatric surgery. Results: During the last 12 months, 46 children aged below 12 years were treated for empyema thoracis: Five (10.86%) were infants, 22 (47.82%) were 1 to 5 years and 19 (41.30%) were 6 to 12 years of age. All the patients presented with complaints of cough, fever and breathlessness of variable durations. Twenty three (50%) children had history of pneumonia and treatment prior to development of empyema. Thirty five (76.08%) children had right-sided and 11 (23.91%) had left-sided empyema. Thirty nine (84.78%) children were successfully treated with tube thoracostomy, systemic antibiotics and other supportive measures. Seven (15.21%) children failed to respond with above and needed decortications. Most commonly isolated bacteria were Pseudomonas (n = 12) and Staphylococcus aureus (n = 7). The average length of hospital stay in patients with tube thoracostomy was 15.35 days, and in patients who needed decortications was 16.28 days following thoracotomy. There was no mortality amongst above treated children. Conclusions: Majority of children with empyema thoracis are manageable with tube thoracostomy, antibiotics, physiotherapy and other supportive treatment. Few of them who fail to above measures need more aggressive management.